Laccase: a multi‐purpose biocatalyst at the forefront of biotechnology. Issue 6 (3rd October 2016) - Mate, Diana M.; Alcalde, Miguel
Summary: Laccases are multicopper containing enzymes capable of performing one electron oxidation of a broad range of substrates. Using molecular oxygen as the final electron acceptor, they release only water as a by‐product, and as such, laccases are eco‐friendly, versatile biocatalysts that have generated an enormous biotechnological interest. Indeed, this group of enzymes has been used in different industrial fields for very diverse purposes, from food additive and beverage processing to biomedical diagnosis, and as cross‐linking agents for furniture construction or in the production of biofuels. Laccases have also been studied intensely in nanobiotechnology for the development of implantable biosensors and biofuel cells. Moreover, their capacity to transform complex xenobiotics makes them useful biocatalysts in enzymatic bioremediation. This review summarizes the most significant recent advances in the use of laccases and their future perspectives in biotechnology. Abstract : Laccases are versatile green biocatalyst at the cutting edge of biotechnology. This review summarizes the most significant advances in the use of laccase in different biotechnological settings from organic synthesis or food and paper industries to biomedical applications and beyond.